2021
DOI: 10.3390/ijerph19010443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Activity and Sport on the Inclusion of People with Visual Impairment: A Systematic Review

Abstract: People with visual impairment have greater difficulty in accessing physical activity and sport, and a lack of social interaction is also associated with a risk of exclusion. Work is currently being done to include people with visual impairment through physical activity and sport. However, there is a lack of studies examining the status and overall effectiveness of interventions in the pre- and post-COVID stage. This study aimed to provide solid evidence on the characteristics and effectiveness of interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…If someone has good self-confidence, it will be easy to achieve, and vice versa. If someone gets achievements, then a good sense of selfconfidence will arise in him (Alcaraz-Rodríguez et al, 2021;Carson et al, 2017;Mirandola et al, 2019). It is the same as previous research indicated that many visually impaired children manage to achieve good intellectual achievement if the environment provides opportunities and motivation for visually impaired children to develop (Buckley et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…If someone has good self-confidence, it will be easy to achieve, and vice versa. If someone gets achievements, then a good sense of selfconfidence will arise in him (Alcaraz-Rodríguez et al, 2021;Carson et al, 2017;Mirandola et al, 2019). It is the same as previous research indicated that many visually impaired children manage to achieve good intellectual achievement if the environment provides opportunities and motivation for visually impaired children to develop (Buckley et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, different levels of physical function limitations are expected in patients with VI depending on the severity of the underlying ocular pathology 51 . It should be noted that the regression coefficient of the physical subscale in the crude model was higher than the adjusted models; the confounding effect of age is probably the main reason considering that aging itself is associated with a decreased physical activity due to a decrease in physical strength 52 . In our study, social activities did not have a statistically significant association with VI in the final linear regression model.…”
Section: Discussionmentioning
confidence: 87%
“…This was done iteratively until “search saturation”, that is to say, no new relevant articles could be found. Existing reviews on similar or related topics, if existing ( Alcaraz-Rodríguez et al, 2021 ), were scanned to increase the chance of including all relevant studies. Further, specific target journals were hand-searched for relevant studies.…”
Section: Methodsmentioning
confidence: 99%